REPRESENTATION OF CULTURAL IDENTITY IN LIMAS HOUSE PALEMBANG - Dadang Hikmah Purnama; Mulyanto Mulyanto; Yulasteriyani Yulasteriyani (DIMENSI (Journal of Architecture and Built Environment), 2021)
This study analyzes the limas house as reflect of Palembang cultural identity, which is interpreted as the identity of "as to becoming". The change in the limas house as a cultural marker is adaptive and dynamic following changes in cultural identity, mainly a family structure, kinship relationship, gender, and marital status. This research uses a qualitative method with the structuralism and phenomenological approach. The informant criteria determined purposively. The data was collected using observation, in-depth interviews, and documentation. The study uses structural analysis to find the structure of form and the layout of the limas house. The analysis of cultural studies is carried out to provide context for the dynamics of changes in cultural identity that affect changes in the limas house. The results showed the structure of the limas house reflects the organizing the layout of the house according to family structure, kinship relationship, gender, and marital status as the cultural identity Palembang. The cultural identity is dynamic through the processes of production and reproduction, thus influencing changes in the limas house. The dynamics of change show the limas house can accommodate social continuity. Limas house is an arena that shows cultural identity through building changes that are adaptive to the social processes. Limas house needs to be protected, maintained, and developed through reinterpretation and revitalization in line with the cultural dynamics of the society.